Analysis of Brand Ambassador, Country of Origin And Word of Mouth on Consumer Trust and Purchasing Decisions (Case Study on Non Member Consumers of Herbalife Nutrition Products) - Wijareni, Damarsasi Nur; Adi Nurmahdi (Dinasti International Journal of Digital Business Management, 2023)
This study aims to analyze the exogenous variables of brand ambassador, country of origin as well as word of mouth in the endogenous variables namely consumer trust and purchasing decisions. The research object is consumers (non-members) of Herbalife Nutrition products. The type of research used is descriptive research and uses quantitative methods. The sample size is 185 respondents using a calculation based on five times the number of indicators. The data analysis method uses the Structural Equation Model-Partial Least Square (SEM-PLS). The results of the study show that the variables brand ambassador, country of origin, as well as word of mouth have a significant positive influence on consumer confidence and purchasing decisions. Managerial implications in research is to increase consumer confidence and purchasing decisions.